Penerapan Strategi Bauran Pemasaran Dalam Meningkatkan Penjualan Pada UMKM Keripik Buah Di Kota Malang - Rizkhie, Viga Esa; Nurhajati, Nurhajati; Asiyah, Siti (Jurnal SOLMA, 2024)
One of the home industries processing fruit chips is a type of business that is quite popular with the natives of Malang City. There are various variants of fruit chips produced, namely avocados, oranges, jackfruit, bananas, etc. The purpose of this study is to determine the analysis of the application of marketing mix strategies in increasing sales in fruit chip MSMEs in Malang City. This research is a service through qualitative research with descriptive methods. The results of this study show that these MSMEs offer variants of fruit chips that are popular in Malang City, including avocados, oranges, jackfruit, and bananas, with good marketing potential. The affordable price of the product in the Malang City community market makes this product well received, has fixed channels such as small shops and clean storage. The promotion of MSMEs on social media is quite effective and provides intangible services or directly to consumers.